(3eSGMI bWY GdeNQhW (B( (3GdbWY GdecGaF(B)s - (3EHQGgje Hf SfGf Hf KGHJ Hf bQI Hf eQhGf Hf KGHJ, CHh ESMGb GdMqQGfj Ke GdHZOGOj,J (B335 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3bP cfJ YedJ cJGHkG ai eSGMI gPG GdbWY bOjekG hZjQJ ai Tcd efg TjFkG Ke VGYJ s
(3BNQgG (B:s
(3hPdc eG cGf GdZQV Cf fHjfg s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B36s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B218 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B83 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(2519) s
Keywords: (3GdQjGVjGJs